Induction of labour in low-risk pregnancies before 40 weeks of gestation: A systematic review and meta-analysis of randomized trials. (March 2022) - Dong, Susan; Bapoo, Shakira; Shukla, Minakshi; Abbasi, Nimrah; Horn, Daphne; D'Souza, Rohan
Abstract: This systematic review of 16 randomized trials, which included 8796 pregnancies, did not demonstrate a reduction in caesarean births or perinatal morbidity from induction of labour (IoL) at 39–40 weeks for non-medical indications. However, IoL at 39–40 weeks may be associated with a lower incidence of maternal hypertensive disorders, a shorter duration of the first stage of labour, fewer instances of meconium-stained amniotic fluid, lower mean birth weights, longer duration of (maternal) hospitalization, and higher epidural usage. Until regional data on clinical benefits, resource implications and long-term impact are available, a prudent approach would be to encourage shared decision-making, wherein birthing persons with low-risk pregnancies are given the opportunity to assess the risks and benefits of IoL at 39–40 weeks over expectant management and allowed to consider their decision in the light of their values and preferences and local resource availability. Highlights: Induction of labour (IoL) under 40 weeks may have clinical benefits in some settings, but not in all. Regional data on clinical, resource- and long-term implications are required before IoL under 40 weeks can be recommended. Birthing persons should have access to evidence-based information on the benefits and risks of IoL at 39 weeks. Shared decision-making should consider resource availability and personal values in addition to evidence from trials.